Mortality in COPD patients according to clinical phenotypes - Golpe R; Suárez-Valor M; Martín-Robles I; Sanjuán-López P; Cano-Jiménez E; Castro-Añón O; Pérez de Llano LA (International Journal of COPD, 2018)
Rafael Golpe, María Suárez-Valor, Irene Martín-Robles, Pilar Sanjuán-López, Esteban Cano-Jiménez, Olalla Castro-Añón, Luis A Pérez de Llano Respiratory Medicine Service, University Hospital Lucus Augusti, Lugo, Spain Purpose: Grouping COPD subjects into clinical phenotypes might be useful for the management of the disease, but the clinical implications of such classification are still not totally clear, especially regarding prognosis. The primary objective of this study was to assess whether the mortality rates were different between four predefined clinical phenotypes. Patients and methods: This is a retrospective, observational study carried out at the COPD clinic of a University Hospital. A total of 891 COPD patients were classified, according to the Spanish COPD guidelines, into the following four phenotypes: asthma–COPD overlap (ACO; 75 subjects), nonexacerbator (NONEX; 531 subjects), exacerbator with chronic bronchitis (EXCB; 194 subjects), and exacerbator with emphysema (EXEMPH; 91 subjects). We compared the mortality outcomes between the phenotypes. Results: After a follow-up of 48.4±25.2 months, there were 194 deaths (21.8%). There were significant differences in all-cause mortality between phenotypes. The ACO phenotype had the best long-term prognosis, whereas EXEMPH had the highest risk of death. NONEX and EXCB mortality figures were in between the other two groups. We also found some differences in the causes of death, and patients with EXEMPH were at a higher risk of dying because of COPD itself. The differences in mortality did not seem related to the classification into phenotypes in itself but to disparities in COPD severity and comorbidity load between groups. Conclusion: Classifying COPD patients according to several predefined clinical phenotypes can identify clusters of subjects with different mortality outcomes. Some phenotypes are associated with a specific cause of death. The mechanisms that underlie these differences seem to be related to COPD severity and comorbidities. Keywords: COPD, phenotypes, mortality